O direito à cidadania no espaço urbano: o desafio no deslocamento por transporte público (ônibus) e por transporte alternativo (táxi-lotação) em Boa Vista-RR - Pieve, Evelise Michele Nunes (2018)
The social relations that are established in the city influence in its socio-spatial formation process, as well as in its production process. The city attracts people, investments, trades, businesses and these relationships are also responsible for the space production process. The "typical" capitalist city emerged under the support of the market mechanism, mainly through real estate transactions, in lands, and later in the urban space produced under the impact of the automobile. The capitalist logic that reproduces in the city accompanied by the logic of the real estate market ends up directly influencing the process of uneven socio-spatial formation of the city. It can be said that these are the main factors that influence the deepening of socio-spatial segregation, directing investments in areas of greater potential for the development of capitalist activities to the detriment of others, considered less "profitable" from the point of view of speculative capital. As a result, the city obtains an urban landscape marked by social inequality. Thus, the city becomes increasingly fragmented, commodified, and the production of space, increasingly necessary for the reproduction of capital. In this sense, the struggle for the right to the city is guided by the overcoming of private property of urban space, so that the city can be seen as a work and understood as use value. In this sense, intra-urban circulation is understood as a key point in the dynamics of production and reproduction of the city's space. Therefore, it is also important to overcome the socio-spatial segregation process, a result of the capitalist logic of valorization of the urban space. In this context, the purpose of this dissertation is to analyze the dynamics of the collective transport of Boa Vista, composed of public transport – bus – and alternative transportation – táxi-lotação – and the right to the city to its users. In order to achieve these objectives, it was necessary to collect bibliographical data on the production of urban space, public transportation and the right to the city, as well as analyzes of maps and maps of the city's public transport, questionnaires with users of public transportation and interviews with public agencies, bus companies and táxi-lotação cooperative.